KAJIAN FILOSOFI HUKUM INTERNASIONAL BERDASARKAN PEMIKIRAN BRIAN Z.TAMANAHA â€œ A REALISTIC OF LAWâ€ - Lona Puspita (Normative Jurnal Ilmiah Hukum, 2020)
The statement about whether the law is still being debated, including the existence of international law as law. Therefore, the authors are interested in analyzing the philosophical studies of international law based on Brian Z. Tamanaha's thinking "A Realistic of Law". According to Brian Z. Tamanaha, international law remains a law whether it is moral or immoral because international law was born because of the agreement of countries to regulate life together with the international community.